ANALISIS PENGGUNAAN TEKNOLOGI VIDEO CONFERENCE VIA ZOOM MEETING PADA PEMBELAJARAN INFORMATIKA KELAS VII A MTS NURUL HIKAM - Yuliana, Dyan; Sonia, Ulfatus; Ayani Suparto, Arico (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
The development of information technology has driven transformation in the world of education, one of which is through the use of video conferencing applications in distance learning. Zoom meetings have become one of the platforms that is widely used during the pandemic until now. The results of observations made by researchers in class VII A at MTs Nurul Hikam show that there are situations that require teachers to use Zoom Meetings so that the learning process continues to run effectively, for example when teachers are attending assignments outside the city. The aim of this research is to analyze the effectiveness of using zoom meetings in the informatics learning process in class VII A MTs Nurul Hikam. This research uses a qualitative approach with a case study method. Data collection techniques used include observation, interviews and documentation of teachers and students who are actively involved. The research results show that zoom meetings facilitate quite effective learning interactions even though there are technical obstacles, such as unstable internet connections. The share screen, chat and video call features are considered capable of increasing student involvement in the learning process. Thus, zoom meetings can be an alternative solution in distance learning, especially when teachers cannot be present in person in class.